Dynamic diversification of lignan metabolism in sesame via coordinated oxygenation and glucosylation across germination - Erisa Harada; Yukie Ohba; Eiichiro Ono; Jun Murata; Hiromi Toyonaga; Akira Shiraishi; Toshiaki Azuma; Toshiyuki Waki; Yuto Uegaki; Eri Okamoto; Atsushi Hoshino; Toru Nakayama; et al. (Proceedings of the National Academy of Sciences, 2026)
Sesame ( Sesamum indicum ) seeds accumulate specialized lignans, including (+)-sesamin, (+)-sesamolin, and (+)-sesaminol triglucoside (SL-TG). Although lignan biosynthesis during seed development is well characterized—with SiCYP92B14 recognized as a (+)-sesamin-specific oxygenase—the molecular basis of the metabolic transition during germination, where lipophilic lignans are fully converted into glucosides, remained unclear. Herein, we identify a set of (+)-sesamin oxygenases, SiCYP706V12–V14, cytochrome P450 enzymes (CYPs) that exhibit a broader substrate range than SiCYP92B14. These enzymes oxidize (+)-sesamin and (+)-sesamolin during germination; when acting on (+)-sesamin, SiCYP706V12 produce (+)-sesaminol, whereas SiCYP706V13 and SiCYP706V14 yield (+)-episesaminone. The resulting oxidized lignans are then sequentially and regio-specifically glucosylated by UDP-glycosyltransferases (UGTs), including SiUGT73E4 and SiUGT73CH10 identified in this study, together with previously characterized UGTs. Functional and kinetic analyses revealed that these UGTs differentially process lignans with distinct molecular structures, thereby contributing to glycoside diversity. Notably, analysis of an SL-TG-deficient sesame line indicates that SiCYP706V12, rather than SiCYP92B14, plays a key role in SL-TG biosynthesis during seed development. Yeast two-hybrid assays revealed a physical interaction between SiCYP706V12 and a downstream UGT, suggesting a possible functional association between these enzymes in lignan metabolism. This underscores the overlapping yet distinct roles of CYP and UGT enzymes in coordinating lignan metabolism from seed development through germination. Our work highlights biochemical evolvability as a key factor in the specialization of plant metabolism in response to developmental and environmental cues.